Effects of a Systematic Quality Improvement Process to Decrease Complications in Trauma Patients With Prehospital Peripheral Intravenous Access. Issue 4 (July 2017) - Garrett, Angie; Drake, Stacy A.; Holcomb, John B.
Abstract : Peripheral intravenous (PIV) catheterization is commonly performed, and its complications are costly, may result in serious health issues, and may adversely affect patient satisfaction. At our large urban Level I trauma center, we identified a cluster of 7 PIV complications from prehospital insertions in a 5-month period. Several of the patients developed noninfectious as well as infectious, limb-threatening complications requiring aggressive operative intervention. A performance improvement project was chartered to identify the cause of PIV complications and review current nursing practice. The FOCUS-Plan Do Check Act methodology was used to measure and improve practice. With implementation of interventions and outcomes monitoring, no PIV complications were reported for the subsequent 39 consecutive months. Our findings have implications for more controlled studies to establish best practice at other Level I trauma centers across the country.